Dynamics modeling and shift control of a novel spring-based synchronizer for electric vehicles. (February 2022) - Wang, Yiwei; Wu, Jinglai; Zhang, Nong; Mo, Wenwei
Highlights: The proposed new spring-based synchronizer can compress the engaging time. The influence of parameters on the new synchronizer is analyzed. Several gear shifting control strategies are proposed to reduce the vehicle jerk. Abstract: This paper investigates the gearshift transient response and the shift control of a new spring-based synchronizer used in the automated manual transmission (AMT) for electric vehicles (EVs). The spring-based synchronizer uses torque spring to provide a torque to synchronize the speed difference between the target gear and the shaft, which reduces the wear caused by friction in traditional synchronizer, as well as decreases the engaging time and the vehicle jerk. The dynamics model of a two-speed AMT in EV equipped with the spring-based synchronizer is built in AMESim software, and the shift control model is established in MATLAB/Simulink environment. The simulation results of the dynamics model demonstrate that the spring-based synchronizer reduces the engaging time and the vehicle jerk compared to the traditional synchronizer. Furthermore, the influences of the motor inertia, speed difference, spring stiffness and shift force on the engaging time and vehicle jerk are quantitatively analyzed. Finally, several control strategies of shift force are proposed, including the single-closed loop PI position control, dual-closed loop PI control, and dual-closed loop fuzzy PI control, which further reduce the vehicle jerk.